“Coco Dragon Fruit Pujuksu” (Date Milk Pudding with Dragon Fruit) To Overcome Anemia in Pregnant Women - Usu; Nuning; Mimi Nanda Sari; Riri Handayani; Jeni Purba; Rukmaini (Rajaki of Tulip Medika Publisher, 2025)
Anemia in pregnant women is still one of the significant public health problems in Indonesia. Iron and vitamin C deficiencies are the primary causes of anemia, particularly during the second and third trimesters of pregnancy. Nutritional interventions based on local food are one of the effective and sustainable preventive solutions. This study aims to examine the effectiveness of providing date milk pudding with dragon fruit sprinkled with cheese as an alternative functional food in preventing anemia in pregnant women. The research method employed is a quantitative descriptive approach with an intervention component. The subjects of the study consisted of 12 pregnant women who were the targets of nutrition education and intervention for 7 days at Posyandu (Integrated Health Service Post) Anggrek 2, Pasir Muncang Village, Subang. The results showed that pudding consisting of a combination of dates, dragon fruit, milk, and cheese was well received by all respondents. As many as 91.6% of pregnant women said they liked the taste, texture, and appearance of the pudding, and 83.3% said they wanted to try making it themselves at home. The nutritional content in one serving of pudding includes iron ±2.3 mg, vitamin C ±18 mg, protein ±8 g, and calcium ±175 mg, which have the potential to increase hemoglobin levels. In addition to being a nutritious food intervention, this activity also includes nutrition education and demonstrations of making it that foster community nutritional awareness and independence. In conclusion, date milk and dragon fruit pudding sprinkled with cheese is an innovative, affordable, and potentially replicable nutritional intervention alternative in community-based anemia prevention efforts. Further research is needed to test the biochemical effects on hemoglobin levels.